A sustainable porous composite material based on loofah-halloysite for gas adsorption and drug delivery. (15th July 2022) - Patamia, Vincenzo; Fiorenza, Roberto; Brullo, Ilaria; Zambito Marsala, Massimo; Balsamo, Stefano Andrea; Distefano, Alfio; Furneri, Pio Maria; Barbera, Vincenzina; Scirè, Salvatore; Rescifina, Antonio
Abstract : We present a quick and straightforward synthesis of a composite from inexpensive materials like loofah and halloysite. New biomaterial showed exceptional carbon dioxide adsorption and release capabilities and good potential for resveratrol delivery. Abstract : The development of new advanced polymers has led researchers to look at nature to find new, high-performance, low-cost materials. This work aims to easily functionalize fibers, made up of polysaccharides, of loofah with halloysite through crosslinkers. Bio-composites have been extensively characterized using different techniques. The synthesized loofah-halloysite composites have improved CO2 adsorption properties superior to those of both individual components and materials currently used in industry. In particular, compared to BEA and the MOR zeolites, an improvement in CO2 capture of about 50% and 23%, respectively, was observed. Moreover, the composite investigated in this work showed superior CO2 capture compared to other cellulose-based and sustainable materials. Furthermore, the presence of halloysite also increased the mechanical properties of the cellulosic polymer. The new cellulose composites have proved to be excellent candidates for the delivery of resveratrol, maintaining its anticancer activity. The results underline the synergistic effect of functionalization on increasing the adsorption properties compared to the starting materials and the possibility of using this eco-sustainable and low-cost porous system in various fields such as gas adsorption and drug administration.